Development of an Instructional Information System Prototype for Use in the Teaching and Development of Nursing Diagnostic Skills - Bloom, K. C. (1988)
An interdisciplinary project was instituted in 1986 for the development and testing of an instructional system to be used in a nursing curriculum for teaching and developing the diagnostic skills of undergraduate nursing students. The system serves two major functions: to assist students in learning and becoming proficient in the diagnostic process and to assist educators in evaluating the students' learning.